Gaining Students’ Literacy through Local Wisdom of Blitar: Implementing of Gerakan Literasi Sekolah (GLS) - Ida Putriani; Ervika Dewi Wahyuni; Siyono Siyono (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This study aimed to explore the implementation of literacy activities in elementary school using children's literature through local wisdom of Blitar. Case study methods were applied in this research. The participants of this research were students from grades I until grade VI at Elementary School Sukorejo 1 Blitar. Collecting data used observation, interview, and documentation. The results showed that the implementation of literacy in elementary schools was carried out as a habituation procedure to read in literacy programmes. Planning literacy program was the most important part in the consistency of literacy implementation. The implementation literacy of children's literature on the local area of Blitar begins with the preparation of the program by the teacher, the implementation of activities with two methods, namely self-reading and reading aloud, and the evaluation literacy program conducted every two months. Keywords: Students’ Literacy, Gerakan Literasi Sekolah (GLS), Literary Local Wisdom